PENGARUH KEADILAN ORGANISASIONAL DAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP KEPUASAN KERJA KARYAWAN DREAMWALK LEMBONGAN BEACH CLUB MARINE & ADVENTURE - Artami, Ni Komang; Adiandari, Ade Maharini (Jurnal MBE Manajemen Bisnis, Equilibrium, 2023)
This study aims to determine the effect of organizational justice and Perceived Organizational Support simultaneously or partially on job satisfaction of employees of Dreamwalk Lembongan Beach Club Marine & Adventure. With a total sample of 54 respondents. Testing the instrument using validity and reliability tests. The data analysis technique used in this research is multiple linear analysis, determination analysis, F test and t test using IBM SPSS Statistics 25.0 for windows application. The results of this study indicate that: (1) The effect of organizational justice simultaneously has a positive and significant effect on employee job satisfaction, (2) The influence of organizational justice partially has a positive and significant effect on employee job satisfaction, (3) Perceived organizational support partially positive and significant effect on employee job satisfaction.